1992
DOI: 10.1063/1.462852
|View full text |Cite
|
Sign up to set email alerts
|

Interoscillator coupling effects on the OH stretching band of liquid water

Abstract: We have studied the OH stretch spectrum in water to explore the effects of interoscillator coupling. Both H2O, which may have significant intra and intermolecular coupling, and dilute HOD in D2O, which is isotopically decoupled, were studied over a broad range of temperature from −33 °C to 160 °C. By adding a small amount of a calibration dopant, we obtained quantitative spectra. We found interoscillator coupling plays a large role at all temperatures. At high temperature, intramolecular coupling contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 20 publications
6
92
0
Order By: Relevance
“…24 They found that the key differences between bulk and confined water are a general blue-shifting of the spectrum along with the appearance of a shoulder on the high-frequency side. They also observed a decrease in the red-shifted shoulder around 3200 cm −1 that appears in the neat H 2 O spectrum, 77,78 but is absent in our simulated spectra for HOD/D 2 O.…”
mentioning
confidence: 77%
“…24 They found that the key differences between bulk and confined water are a general blue-shifting of the spectrum along with the appearance of a shoulder on the high-frequency side. They also observed a decrease in the red-shifted shoulder around 3200 cm −1 that appears in the neat H 2 O spectrum, 77,78 but is absent in our simulated spectra for HOD/D 2 O.…”
mentioning
confidence: 77%
“…Between 18 and 120 THz (600-4000 cm À1 ), pure water exhibits two noticeable dispersions assigned to the H-O-H bending (49 THz) and O-H stretching (~100 THz) (99). Especially, the latter is strongly coupled with intermolecular HB dynamics (49)(50)(51)(52)(55)(56)(57)(58), and in general, the O-H stretching frequency red-shifts as the intermolecular HB becomes stronger (100)(101)(102)(103)(104). On the other hand, the complex dielectric constant of albumin crystal exhibits the several amide bands (66,105,106) between 30 and 50 THz, the C-H stretching (87 THz) (107), and N-H stretching (~100 THz) (66) in the MIR region.…”
Section: Derivation Of O-h Stretching Of Hydration Watermentioning
confidence: 99%
“…In addition, an O-H stretching vibration around 100 THz (3330 cm À1 ) has been conventionally used as an index to estimate the HB strength (49)(50)(51)(52)(53)(54)(55)(56)(57)(58). In general, the stronger the HBs that a given water molecule establishes with its neighbors, the more red-shifted is the O-H stretching frequency (49,57,58).…”
Section: Introductionmentioning
confidence: 99%
“…Others have argued that the complications of intramolecular and intermolecular vibrational coupling make simple interpretations of these spectra difficult [7-9, 69, 70, 72]. In fact, many believe that the lower-frequency peak in the VV Raman spectrum arises from a collective mode [7,69,70,72].…”
Section: A Line Shapesmentioning
confidence: 99%